Evaluation of palliative care costs for neurological patients in a hospital of the Unified Health System - Carina Soares MACIEL; Michelle Melgarejo DA-ROSA; Michelly Cristiny PEREIRA (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde)
Objective: To quantify daily direct costs through absorption costing and the demographic profile of neurological patients receiving palliative care (PCs) at a hospital in the Unified Health System. Methods: Convenience sample composed of 132 individuals admitted to Hospital Mestre Vitalino (HMV), in Caruaru-Pernambuco, with a diagnosis of neurological diseases, over 18 years of age and a favorable opinion for PCs, admitted to the Intensive Care Unit (ICU) and/or wards of HMV, and who had a favorable opinion from the PCs committee to start this type of care at HMV between 01/01/2019 and 12/31/2019, evolving to death in the unit in the same period. Average daily costs were adjusted by purchasing power parity1 and the American Consumer Price Index2, later converted to US dollars according to the exchange rate in effect on September 13, 2024. Results: The time interval between the start of PC and death had an average of 18.3 days. After the institution of this assistance, there was a 27% reduction (p<0.0001) in daily costs in the wards for the group evaluated. The reduction in costs for PC patients admitted to the Intensive Care Unit was not statistically significant for the sample evaluated, just as the demographic variables did not statistically influence the costs. The total cost was US$ 211,981.49 to US$ 164,562.37 in daily rates after the institution of PCs for the entire sample during 2019. Conclusion: The present study found a significant reduction in direct hospitalization costs for patients after insertion into PCs, mainly for those who were inserted into PCs from the beginning of the hospitalization period and who were allocated to wards.